Eﬀects of Inhalation of Hydrogen Gas on Oxygen Uptake during Exercise Test in Humans - HORI, Amane; HOTTA, Norio; OGATA, Hisayoshi; KONDO, Takaharu (Japanese Journal of Sports and Health Science, 2020)
The purpose of this study was to investigate the effects of molecular hydrogen (H2) gas inhalation on the oxygen uptake during an incremental exercise test performed on a cycle ergometer. This study was designed as a single-blind, randomized, controlled trial. Eight men and one woman volunteered to perform an incremental cycling exercise test while inhaling one of two kinds of gases: 1 % H2 gas (H2 trial) or air (control trial). In both trials, the workload was gradually increased by 20 W every minute until volitional fatigue set in. Respiratory parameters were measured during the test using a breath-by-breath gas analyzer. Blood samples were collected from the subjects’ fingertips before, during, and immediately after the end of the exercise to evaluate the systemic redox status. We found that: 1) the H2 trial signifi cantly augmented oxygen uptake (VO2) response to exercise after 20 W as compared with that observed in the control trial; 2) the H2 trial significantly increased peak oxygen uptake (VO2peak) as compared with that of control trial; and 3) the H2 trial also signifi cantly shifted to a reduced state in the systemic redox balance, immediately after the exercise ended as compared with the control trial, suggesting the H2 trial reduced oxidative stress. In conclusion, inhalation of H2 gas signifi cantly increased the VO2 response and VO2peak during incremental exercise. These results may suggest that inhalation of H2 gas improves mitochondrial function during exercise.